The case for pragmatic psychology - Fishman, Daniel B. (New York University Press, 1999)
Web Site The interested reader is urged to contact the author and join a Pragmatic Psychology Dialogue Group at the following web site: http://www.rci.rutgers.edu/~dfishman/ "At long last, a tightly reasoned, thoroughly grounded treatise showing that complex social programs can be understood far more profoundly and usefully than past mindsets have allowed."--Lisbeth B. Schorr, author of Common Purpose: Strengthening Families and Neighborhoods to Rebuild America"Fishman creates a new paradigm for advancing clinical science. Every mental health professional aspiring to be accountable and a scientist practitioner in their work should be aware of the ideas in this readable and entertaining book."--David H. Barlow, editor of Clinical Handbook of Psychological Disorders "Daniel Fishman cuts through rhetoric with clear writing and a razor-sharp wit. The chapter on education is like the welcome beam of a lighthouse in a fog."--Maurice J. Elias, coauthor of Social Problem Solving: Interventions in the Schools "Fishman makes the case for a pragmatic psychology in unusually lucid and forceful prose. This book should be read not only by professional psychologists but by anyone interested in the future of mind-related science." --John Horgan, author of The End of Science: Facing the Limits of Knowledge in the Twilight of the Scientific Age "Fishman's liberating insights will free his readers to set aside the intellectual quandaries that plague philosophers and psychologists at the end of the 20th century, and turn back with confidence to the practice of their work."--Stephen Toulmin, author of Cosmopolis: The Hidden Agenda of Modernity "As we try to steer a course through the public policy debates of the 21st century, Fishman's pragmatic psychology for enhancing human services provides a far-reaching new resource for meeting this challenge." --Pat Schroeder, President and CEO, Association of American Publishers. Former Congresswoman from Colorado. About the Book A cursory survey of the field of psychology reveals raging debate among psychologists about the methods, goals, and significance of the discipline, psychology's own version of the science wars. The turn-of-the-century unification of the discipline has given way to a proliferation of competing approaches, a postmodern carnival of theories and methods that calls into question the positivist psychological tradition. Bridging the gap between the traditional and the novel, Daniel B. Fishman proposes an invigorated, hybrid model for the practice of psychology-a radical, pragmatic reinvention of psychology based on databases of rigorous, solution-focused case studies. In The Case for Pragmatic Psychology, Fishman demonstrates how pragmatism returns psychology to a focus on contextualized knowledge about particular individuals, groups, organizations, and communities in specific situations, sensitive to the complexities and ambiguities of the real world. Fishman fleshes out his theory by applying pragmatic psychology to two contemporary psychosocial dilemmas --the controversies surrounding the "psychotherapy crisis" generated by the growth of managed care, and the heated culture wars over educational reform. Moving with ease from the theoretical to the nuts and bolts of actual psychological intervention programs, Fishman proffers a strong argument for a new kind of psychology with far-reaching implications for enhancing human services and restructuring public policy